The Effects of Combined Virtual Reality Exercises and Robot Assisted Gait Training on Cognitive Functions, Daily Living Activities, and Quality of Life in High Functioning Individuals With Subacute Stroke - Akinci, Murat; Burak, Mustafa; Kasal, Fatma Zehra; Ozaslan, Ezgi Aydin; Huri, Meral; Kurtaran, Zeynep Aydan (Sage Publications Inc, 2024)
Stroke is a global health concern causing significant mortality. Survivors face physical, cognitive, and emotional challenges, affecting their life satisfaction and social participation. Robot-assisted gait training with virtual reality, like Lokomat, is a promising rehabilitation tool. We investigated its impact on cognitive status, activities of daily living, and quality of life in individuals with stroke. Between September 2022 and August 2023, we exposed 34 first stroke patients (8 women, 26 men; M age = 59.15, SD = 11.09; M height = 170.47, SD = 8.13 cm; M weight = 75.97; SD = 10.87 kg; M days since stroke = 70.44, SD = 33.65) in the subacute stage (3-6 months post-stroke) to Lokomat exercise. Participant exclusion criteria were Lokamat exercise inability, disabilities incompatible with intended measurements, and any cognitive limitations. The Control Group (CG) received conventional physiotherapy, while the Lokomat Group (LG) received both conventional physiotherapy and robot-assisted gait training with virtual reality, administered by an occupational therapist. Evaluations were conducted by a physiotherapist who was unaware of the participants' group assignments and included assessments with the Montreal Cognitive Assessment, Lawton Brody Instrumental Activities of Daily Living Scale, and Stroke Specific Quality of Life Scale (SS-QoL). Both groups demonstrated an improved quality of life, but the LG outperformed the CG with regard to SS-QoL (p = .01) on measures of Energy (p = .002) and Mobility (p = .005). Both groups showed improvements in cognitive functioning (p < .001) with no between-group difference, and in activities of daily living (p < .05) for which the LG was superior to the CG (p = .023). Thus, adding robot-assisted gait training with Lokomat and virtual reality improved self-reported quality of life and daily activities at levels beyond conventional physiotherapy for patients in the subacute stroke phase. An incremental impact on cognitive functions was not evident, possibly due to rapid cognitive recovery or this was undetected by limited cognitive testing.
Keywords: cognitive functions; subacute stroke; robot assisted gait training